ANALYSIS OF THE PRABOWO-GIBRAN C ANALYSIS OF THE PRABOWO-GIBRAN CAMPAIGN MODEL IN THE 2024 PRESIDENTIAL AND VICE PRESIDENTIAL ELECTIONS - Nadeak, Frans; Nabila (Sociae Polites, 2024)
The 2024 elections in Indonesia have received considerable attention, especially in relation to the campaign strategies carried out by various political candidates. The purpose of this research is to analyze and describe the campaign trends of the Prabowo Gibran pair in the 2024 Election. This research uses qualitative methods with data collection techniques through interviews and literature studies. The results of this study show that answering problems related to the trend of political campaign models carried out by Prabowo-Gibran in the 2024 Presidential and Vice Presidential Elections and interest in young people. Researchers hope that this research can provide recommendations for references with the same material and campaign model trends that can be reused in the next presidential and vice presidential elections with the delivery of a clear vision and mission narrative.